Towards a Comparative Study of Authentication Mechanisms for Low-Resource Internet of Things Devices - Sousa, Joel; Tomaz, Emerson B.; Araújo, Allysson Allex (Anais Estendidos do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2024: Anais Estendidos do XX Simpósio Brasileiro de Sistemas de Informação, 2024)
Authenticity represents an essential facet of information security explored across various Information Systems (IS), including Internet of Things (IoT) devices in Industry 4.0. However, deploying authentication mechanisms in specific IoT devices poses significant challenges, particularly for those with energy, memory, and computational power constraints. Given this context, this ongoing research project aims to compare conventional authentication mechanisms for low-resource IoT devices and identify the most efficient one among them. As an initial result, this paper aims to present our methodological scope and discuss preliminary empirical results derived from a computational experiment using the Non Interactive Zero Knowledge Proofs (NIZKP), algorithm in Arduino Nano. This research seeks to enhance the comprehension of authentication mechanisms in low-resource IoT devices, thus facilitating better decision-making processes in IS settings and contributing to academia and practice.